STEM, a Non-Place for Women? Evidences and Transformative Initiatives - Eva Cernadas; Eva Aguayo; Manuel Fernández-Delgado; Encina Calvo-Iglesias (Social Sciences, 2025)
Numerous studies, diagnoses, and projects have been carried out in recent years to analyze the low female presence in STEM studies. However, progress has been limited, and the female presence is still low in certain degrees related to information and communication technologies, physics, and engineering. Many of the actions have been aimed at attracting women to these fields, but few have tried to change the culture of these disciplines, which make them a non-place for women. This paper analyses the measures carried out in Spanish public universities, and specifically at the University of Santiago de Compostela, to contribute to making these disciplines a place for women. Computer engineering workshops for primary and secondary education are proposed, incorporating a gender perspective. These transformative activities were highly valuated and welcomed by non-university teachers. The ideas inspiring these initiatives might help both to attract girls to STEM degrees and to generate gender equality environments, in order to change the androcentric culture of this field.